The roles of intrinsic motivation and capability-related factors in cognitive effort-based decision-making - Randez, Alyssa; Hélie, Sébastien (Frontiers in Psychology, 2024)
The decisions made in everyday life can greatly impact our overall quality of life, and understanding how these decisions are made can highlight different types of motivations. While most theories involved in human decision-making consider the requirement costs (e.g., time, cognitive resources) against the benefits of performing an action (e.g., money, internal satisfaction), how these different factors are valued is still being investigated. This paper furthers this investigation by focusing on demand preferences when the options were tailored to each individual. Results suggested that individual differences in pursuing effortful tasks may depend on the task itself as well as how demanding options are relative to each other. The results of this study may have the potential to further uncover motivations behind effort exertion by highlighting how experimental and educational program designs can influence decisions beyond their challenge or demand-related factors. That is, people may base decisions on factors related to the tasks themselves. The authors of this manuscript believe that this study would be of interest to Frontiers because it highlights human decision making in a way tha t can be used across disciplines to create effortencouraging program designs.